2003
DOI: 10.1021/ja036712h
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Protein Immobilization by Staudinger Ligation

Abstract: The Staudinger ligation between an azido-protein and a phosphinothioester-derivatized surface is demonstrated to be an effective means for the site-specific, covalent immobilization of a protein. Immobilization yields of >50% are obtained in <1 min, and immobilized proteins have >80% of their expected activity. No other method enables more rapid immobilization or a higher yield of active protein. Because azido-peptides and azido-proteins are readily attainable by synthesis, biosynthesis, or semisynthesis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
173
0
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(182 citation statements)
references
References 15 publications
2
173
0
7
Order By: Relevance
“…Typically these methods rely on the labeling of the protein of interest with an azide moiety. In the Staudinger ligation, the reaction of an azide with a phosphine forms an intermediate iminophosphorane (azaylide) that can then react with electrophiles to give a variety of products [27,28]. The generation of an iminophosphorane is typically followed by reaction with an ester to form a stable amide bond.…”
Section: Classical Covalent Immobilization Methodsmentioning
confidence: 99%
“…Typically these methods rely on the labeling of the protein of interest with an azide moiety. In the Staudinger ligation, the reaction of an azide with a phosphine forms an intermediate iminophosphorane (azaylide) that can then react with electrophiles to give a variety of products [27,28]. The generation of an iminophosphorane is typically followed by reaction with an ester to form a stable amide bond.…”
Section: Classical Covalent Immobilization Methodsmentioning
confidence: 99%
“…Such type of linkage can be then fulfilled by chemical ligation strategies. While a number of research groups have demonstrated the use of chemical ligations to fix peptides, carbohydrates and other small biomolecules on glass surfaces (via aldehydemediated ligation, [70] native chemical ligation, [71] Staudinger ligation [72][73] and click chemistry [74] ), only a few reports have shown a direct immobilization of an entire protein onto glass slides through chemoselective reaction. Coleman and co-workers have recently described the use of EPL for the creation of microarrays of proteins by covalent attachment of thioester tagged proteins onto a modified glass surface containing an N-terminal Cys poly(ethylene glycol) linker.…”
Section: Application Of the Chemical Ligation Methods For Preparationmentioning
confidence: 99%
“…Controlled orientation, site-specific immobilization of protein has received considerable attention in many biological fields, such as biomaterials [1][2][3] , biosensors [4][5][6][7][8] and protein arrays [9][10][11][12] , as well as the study of structure-function relationships. 13,14 An essential step for protein immobilization is to construct a well-defined surface exhibiting selective affinity for the desired protein while resisting nonspecific protein adsorption.…”
Section: Introductionmentioning
confidence: 99%